2014
DOI: 10.1590/s0100-736x2014000300001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do quadro eritrocitário e da repercussão do estado anêmico no leucograma de caprinos com verminose gastrintestinal

Abstract: Com o intuito de caracterizar a anemia decorrente da verminose gastrintestinal e avaliar as alterações no leucograma, foram realizadas hemogramas de 96 caprinos da raça Saanen adultos, sendo que 57 destes estavam anêmicos. O diagnóstico da enfermidade foi realizado pelos sintomas característicos da doença como mucosas conjuntival esbranquiçadas, edema submandibular, emagrecimento e pelame arrepiado, confirmados por exame de fezes no qual se detectou a presença de ovos da superfamília Trichostrongyloidea. As am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
3
1
2
Order By: Relevance
“…These values are higher than those obtained in the present study. Birgel et al (2012) reported that aggravation of anemia symptoms in goats of the breed Saanen infected with worms was correlated with neutrophilia, which was not observed in the present study. Normal lymphocyte values were observed for the evaluated lambs (Table 4).…”
Section: Discussioncontrasting
confidence: 90%
“…These values are higher than those obtained in the present study. Birgel et al (2012) reported that aggravation of anemia symptoms in goats of the breed Saanen infected with worms was correlated with neutrophilia, which was not observed in the present study. Normal lymphocyte values were observed for the evaluated lambs (Table 4).…”
Section: Discussioncontrasting
confidence: 90%
“…The haematological indices MCV and MCHC, mostly used for anaemia's classification (Menezes et al 2010, Birgel et al 2014, were significantly distinct from other studies with the species, even for Brazilian regions (Sanches et al 2013). This data has direct relation to the amount of red blood cells and haemoglobin and, consequently, are influenced by physiologic, nutritional, environmental, climatic and management factors (Birgel Jr et al 2001).…”
Section: Resultsmentioning
confidence: 66%
“…The treatments did not differ statistically (p > 0.05) for neutrophils, with the results for these counts showing a slight increase in relation to the upper reference value (10-50%) of JAIN (1993), characterizing mild neutrophilia (Table 2). Neutrophilia is believed to be due to the inflammatory process in the mucosa, determined by gastrointestinal parasites (BIRGEL et al, 2014). The eosinophil count differed (P < 0.05) between the treatments BMs + potato (1g/Kg/lw), BMs + potato (0.5g/Kg/lw), and BMs + moxidectin; however, the results were within the reference values (0-10%) of JAIN (1993).…”
Section: Resultsmentioning
confidence: 69%